The cultural influence on the dissemination of domestic and public violence against women (Revista da Faculdade de Direito, Universidade de São Paulo, 2020)
This article seeks to analyze the influence of the patriarchal culture disseminated in society, originating in the early days, where men and women since conception, accepted a preconceived model of their destiny and their functions in society. What we want to demonstrate is the fact that due to gender stereotypes, the roles between dominator and dominated have been accepted and reproduced over thousands of hundreds of years, in addition to emphasizing that gender violence against women is perpetuated thanks to legitimacy and the myths prescribed by the male/patriarchal society where the subordinate position of women in relation to exploitation and violence was admitted as an intrinsic behavior of men and society, but which has been gradually combated, mainly since the 1988 Constitution, with changes in legislation aimed at protecting minorities.